Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.4049/jimmunol.1003431
|View full text |Cite
|
Sign up to set email alerts
|

Immune Evasion byHelicobacter pyloriIs Mediated by Induction of Macrophage Arginase II

Abstract: Helicobacter pylori infection persists for the life of the host due to the failure of the immune response to eradicate the bacterium. Determining how H. pylori escapes the immune response in its gastric niche is clinically important. We have demonstrated in vitro that macrophage NO production can kill H. pylori, but induction of macrophage arginase II (Arg2) inhibits inducible NO synthase (iNOS) translation, causes apoptosis, and restricts bacterial killing. Using a chronic H. pylori infection model, we determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(116 citation statements)
references
References 54 publications
6
110
0
Order By: Relevance
“…H. pylori PMSS1 and SS1 were cultured as previously described (25,42). PMSS1 was used for acute in vivo and ex vivo infections because it is the original clinical isolate and retains its ability to translocate the oncoprotein, CagA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…H. pylori PMSS1 and SS1 were cultured as previously described (25,42). PMSS1 was used for acute in vivo and ex vivo infections because it is the original clinical isolate and retains its ability to translocate the oncoprotein, CagA.…”
Section: Methodsmentioning
confidence: 99%
“…Male mice were selected because previous studies have demonstrated that female mice are protected from gastric damage during H. pylori infection (60). Sample sizes were based on previous studies (14,25,42,61). No other selection criteria were used in these studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used clustered charged-to-alanine mutagenesis and structural modeling to address this question, and generated four new mutants of yeast eIF5A. Chaturvedi et al (2012) who previously reported the importance of utilizing l-arginine as a host response to the gastric pathogen Helicobacter pylori, now show that generation of antimicrobial nitric oxide (NO) by inducible NO synthase (iNOS), which is dependent on l-arginine availability, is limited by competition with arginase II activity (Lewis et al 2011) and upregulation of ODC. Spermine blocks l-arginine uptake into macrophages (Chaturvedi et al 2010) and SMO mediates DNA damage in gastric epithelial cells.…”
Section: Editorialmentioning
confidence: 99%
“…The authors show that generation of antimicrobial nitric oxide (NO) by inducible NO synthase (iNOS), which is dependent on L-arginine availability, is limited by competition with arginase II activity (Lewis et al 2011) and upregulation of ornithine decarboxylase. Spermine blocks L-arginine uptake into macrophages (Chaturvedi et al 2010) and SMO mediates DNA damage in gastric epithelial cells.…”
mentioning
confidence: 99%